2018
DOI: 10.1186/s12889-018-5425-6
|View full text |Cite
|
Sign up to set email alerts
|

Substance use and suicidal ideation and behaviour in low- and middle-income countries: a systematic review

Abstract: BackgroundUnderstanding relationships between substance use and suicidal ideation and behaviour (SIB) has important public health implications for suicide prevention in low- and middle-income countries (LMICs), where 75% of suicides occur. This systematic review explored the associations between substance use and SIB in LMICs.MethodsWe searched five databases using a combination of keywords for substance use, SIB and LMICs to identify English-written quantitative studies published between January 2006 and Febr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
66
1
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(84 citation statements)
references
References 132 publications
(301 reference statements)
8
66
1
9
Order By: Relevance
“…The prevalence of psychiatric care among those who did not commit suicide were 1461 (1.1%) in the control group versus 4619 (18.6%) in patients treated for DUD. Figure 2 shows the Nelson-Aalen cumulative incidence of suicide for all four groups (i.e., [1] people with a history of treatment for DUD without psychiatric history, [2] people with a history of treatment for DUD with psychiatric history, [3] people with no history of treatment for alcohol or DUD without psychiatric history, and [4] people with no history of treatment for alcohol or DUD with psychiatric history.…”
Section: Descriptive Statisticsmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of psychiatric care among those who did not commit suicide were 1461 (1.1%) in the control group versus 4619 (18.6%) in patients treated for DUD. Figure 2 shows the Nelson-Aalen cumulative incidence of suicide for all four groups (i.e., [1] people with a history of treatment for DUD without psychiatric history, [2] people with a history of treatment for DUD with psychiatric history, [3] people with no history of treatment for alcohol or DUD without psychiatric history, and [4] people with no history of treatment for alcohol or DUD with psychiatric history.…”
Section: Descriptive Statisticsmentioning
confidence: 99%
“…Several meta-analytic studies have reported an association between substance use, including alcohol and illicit drug use on the one hand, and suicidal ideation, suicide attempts, and suicide death on the other [3,4]. A recent meta-analysis found that in case-control psychological autopsy studies, the presence of a drug use disorder (DUD) was associated with a 7-fold increase in suicide [5].…”
Section: Introductionmentioning
confidence: 99%
“…Bowden et al ( 97 ) in a large cohort study of 2,803,457 residents of Wales, UK, highlighted the relationship between emergency alcohol-related hospital admission and the increased risk of suicide. A recent systematic review of 108 studies explored the associations between substance use and suicide risk in low- and middle-income countries ( 98 ) demonstrated an association between alcohol use, intoxication and pathological use of alcohol, tobacco, cannabis, illicit drugs and non-medical use of prescription drugs and suicide risk. Furthermore, Choi et al ( 99 ) examined blood alcohol concentration (BAC) among suicide decedents aged 50 years or older.…”
Section: Lifestyle Behavior and Suicide In Young Adults And Adultsmentioning
confidence: 99%
“…Even though suicidal behavior has a high prevalence among medical students, most available research evidence comes from developed countries, and little attention is paid to lower-middle-income and lower-income countries [26]. To the best of our knowledge, there has been no published study on suicide ideation, attempt, and associated factors among medical students in Ethiopia.…”
Section: Introductionmentioning
confidence: 99%